Gender, effort-reward imbalance at work, and burnout: Findings from a developing Caribbean country. Issue 6 (7th August 2017) - Devonish, Dwayne
Abstract : Purpose: The purpose of this study is to examine gender as a key moderator in the relationship between effort-reward imbalance (ERI) and burnout among employees in Caribbean workplaces. Design/methodology/approach: Based on a survey sample of 323 employees in a small developing country in the Caribbean, this study tested the hypothesis that the stressor–strain relationship (captured by ERI and burnout) is stronger for women than for men. Findings: The results revealed that the effect of high effort-low rewards (i.e. ERI) on burnout among females was significantly larger than its effect on burnout for males. In contrast, high effort-high rewards were significantly associated with higher burnout levels for males. Research limitations/implications: The study used a cross-sectional approach using self-report measures of burnout, effort and rewards. Practical implications: Management in organisations should ensure that male and female employees' efforts and contributions at work are appropriately and fairly rewarded as a means of reducing negative effects of ERIs. Originality/value: The study examined how gender moderated the adverse effects of a popular work-stress model on employee health in a developing country context.